Contribution of speed and agility to dribbling ability - Pra Adha, Ozha Wahyu; Fadlan, Abdur Rohim; Helmi, Dio Septiyan; Mayangsari, Rina; Cahyani, Firunika Intan; Meirafoni, Yummi (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2025)
Problems: The problem of this research was identified because students often lose the ball when passing opponents, less than optimal dribbling speed so that it is easy to be chased by opponents, and low agility which causes movements to be easy to read. Purpose: This study aims to test the contribution of speed and agility to the ability of soccer dribbling in students. Methods: This study uses a quantitative approach through a correlational method, this study seeks to provide a scientific understanding of the relationship between physical variables (speed and agility) with technical abilities (dribbling). This study involved 26 students as research samples through a total sampling technique. The instruments used include a 30-meter running test for speed, a dogging run test for agility, and a dribbling test with 7 obstacles. Data analysis was carried out using correlation techniques with SPSS software version 24. Results: The results of the descriptive analysis showed that the average speed time was 5.68 seconds, agility 6.49 seconds, and dribbling 24.58 seconds. Students with the best speed and agility also recorded the fastest dribbling results, which indicates a positive relationship between basic physical abilities and dribbling skills. Conclusion: This study concluded that increasing speed and agility can significantly contribute to dribbling effectiveness. This finding is important as a basis for designing more targeted and evidence-based soccer training programs